Effects of interface atomic rearrangement on band alignments in Ge/a-Al2O3/Au heterostructures from first-principles - Eunjung Ko; Choi, Jung-Hae (Elsevier BV, 2022)
We study the effects of interface atomic rearrangement on the band alignments of Ge/a-Al2O3/Au structures as a prototype for metal-amorphous oxide-semiconductor systems with a nanometer-thick oxide from first principles. The significant atomic rearrangement at Ge/a-Al2O3 and a-Al2O3/Au interface regions results in a slanted band alignment in the oxide region, which cannot be described by the numerical Schottky-Mott model. The band alignment is explained by considering the interface dipoles due to the interface-work-function change and the interface effective charge density, which were previously dismissed as unimportant. On the other hand, the effect of the interface dipole on the band alignment originating from the interface-charge-density difference is found to be negligible.